PERKAWINAN HUKUM ADAT SUKU ANAK DALAM DITINJAU DARI UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN DI DESA SANGLAP KECAMATAN BATANG CENAKU KABUPATEN INDRAGIRI HULU - Candra. H, Limboy Alex; Bachtiar, Maryati; ', Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Tribe Anak Dalam (SAD) or often also called the Kubu Tribe, is a group of peoplewho live in the jungle of the jungle with the pattern of moving (Nomad), Tribe Anak Dalam /Orang Rimba have their own custom law or tradition that has been inherent in them which istheir life reference or guide. in the Tribe Children In husbands can marry the youngersiblings of his wife as long as the husband is still able to support the birth and the inner wifeor also called the relationship semenda. From the background, the authors conducted a studytitled